2010
DOI: 10.3113/fai.2010.0329
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula and Pseudoaneurysm of the Posterior Tibial Artery After Calcaneal Slide Osteotomy: A Case Report

Abstract: For information on pricings and availability of reprints, call 410-494-4994, x232. Fig. 2: Magnetic resonance angiogram revealing an arteriovenous malfor mation with a pseudoaneurysm measuring 1.8 x 3 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…Like Doty et al and Greene et al, we suggest that calcaneal osteotomy should be completed through the medial calcaneal cortex in a carefully controlled manner because of the proximity of vascular structures. 9,15 In this study, the average closest point between line A and the LPA was 59.3% when expressed as a percentage of the total distance of line A from the posterosuperior aspect of the calcaneal tuberosity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Like Doty et al and Greene et al, we suggest that calcaneal osteotomy should be completed through the medial calcaneal cortex in a carefully controlled manner because of the proximity of vascular structures. 9,15 In this study, the average closest point between line A and the LPA was 59.3% when expressed as a percentage of the total distance of line A from the posterosuperior aspect of the calcaneal tuberosity.…”
Section: Discussionmentioning
confidence: 57%
“…8 One of the complications reported after calcaneal osteotomy is pseudoaneurysm of the LPA. 9,10 Progressive enlargement of an untreated LPA pseudoaneurysm can compromise adjacent nerves and vessels and lead to ulceration and ultimately rupture 11 if the laceration…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that completion of the osteotomy on the medial side should be performed with caution. Doty et al 2 published a case report which described an arteriovenous fistula and pseudoaneurysm after calcaneal slide osteotomy. Ptaszek et al 12 described the development of a lateral plantar artery pseudoaneurysm after calcaneal osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Before performing this osteotomy in clinical practice, it seemed wise to perform an anatomic study to evaluate the relation of the osteotomy with the medial neurovascular structures especially since there have been several case reports describing damage to neurovascular structures after calcaneal osteotomy. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Se han reportado fístulas arteriovenosas y parálisis del nervio tibial. 87,88,89 Técnica quirúrgica: la incisión se inicia por debajo del maléolo lateral en un ángulo aproximado de 45 grados, evitando el nervio sural y sus ramas así como los tendones peroneos. La disección continúa hasta el hueso, los separadores de Hohmann se colocan en posición dorsal y plantar alrededor del hueso para proteger las estructuras y los tejidos blandos.…”
Section: Osteotomía Medializante De Koutsogiannisunclassified